Valuasi Lingkungan TCM di Bogor Mini Zoo Kota Bogor - Ruti Nurul Hidayati; Ribut Lupiyanto; Nurhasanah Nurhasanah (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Bogor Mini Zoo is one of nature tourism area that must be appreciated by economic value with non market based. Bogor Mini Zoo have some advantages as animal park for local communities, students education and research. This ecotourism located in Pamoyanan, Bogor City. This study aims to determine variabels that are influences demand function curve, estimate willingness to pay of enviromental services and consumer surplus. This study is a survey research conducted using the method of Travel Cost Method that will analyze by multiple regression, approach of willingness to pay and consumer surplus. The result showed that economic value of environmental services can increase continual environmental protection in Bogor Mini Zoo. This study also explained that economic value of environmental services will support quality improvement of environment sustainability in Bogor Mini Zoo that can provides great economic benefit by improvement of animal park fasilities, ecotourism public fasilities and environmental quality. That matter will implement with collaboration of visitors, local communities, stakeholders and local government. This study of economic value of environmental services in animal park was still limited so it has important role for ecotourism development.